Geguritan Singandalang: Analisis Struktur Dan Nilai - Wirayasa, I Kadek; Supatra, I Nyoman; Duana Sutika, I Nyoman (Humanis; Vol 17 No 3 (2016), 2016)
Geguritan Singandalang is a Bali literary work which contains about loyalty I Singandalang to Ni Layonsari who meet the exam when you just got married. Research on Geguritan Singandalang analyzed using structural theory. Geguritan building structures, namely forma structure and narrative structure. Analysis of the structure will also be equipped with an analysis of the value that can be used as guidelines in this life. This research was carried out over several stages, namely: (1) step of providing data using a method of reading, which is supported by engineering transliteration, translation techniques and recording techniques, (2) the stage of data analysis using qualitative methods are supported using the technique of descriptive analytic, (3) the stage of presentation of the results of data analysis using informal methods that are supported by engineering deductive and inductive techniques. Geguritan Singandalang structural analysis include: (1) the structure forma: code language and literature, style, language diversity. Geguritan Singandalang use only one type pupuh, namely pupuh panglipur using a variety of language Bali kepara. (2) the structure of the narrative include: incident, plot, setting, character and characterization, theme and mandate. There are eleven incidents in Geguritan Singandalang. Using a straight furrow. Background includes background place, time setting and background ambience. Figure consists of the main characters, secondary characters and complementary figures. Penokohannya views analytically and dramatic with character terms of three dimensions: the physiological, psychological and sociological. The theme used, which is about loyalty. Analysis of the value in Geguritan Singandalang include religious values ??(philosophy, decency, ceremonial), the value of loyalty, educational value, social value and aesthetic value.